2005
DOI: 10.1176/appi.ajp.162.6.1221
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind, Placebo-Controlled Study of Dialectical Behavior Therapy Plus Olanzapine for Borderline Personality Disorder

Abstract: A combined psychotherapeutic plus pharmacological approach appears to lower dropout rates and constitutes an effective treatment for borderline personality disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
1
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(83 citation statements)
references
References 6 publications
3
69
1
10
Order By: Relevance
“…Six of these studies compared olanzapine to placebo. These studies are Bogenschutz and Nurnberg 31 (n = 40); Linehan et al 32 (olanzapine was added to psychotherapy, n = 24); Schulz et al 33 (n = 314); Soler et al 34 (all patients were in DBT, n = 60); Zanarini and Frankenberg 35 (n = 28); and Eli Lilly 36 (n = 301). Of the remaining three studies, one compared olanzapine to haloperidol (Shafti and Shahveisi, 37 n = 28); one compared olanzapine to sertraline (Jariani et al, 10 n = 120 [all patients were on methadone maintenance therapy]); and one with three different arms of treatment 38 compared olanzapine to fluoxetine (n = 30), then olanzapine to olanzapine plus fluoxetine (n = 31), and finally fluoxetine to fluoxetine and olanzapine (n = 29).…”
Section: Olanzapinementioning
confidence: 99%
“…Six of these studies compared olanzapine to placebo. These studies are Bogenschutz and Nurnberg 31 (n = 40); Linehan et al 32 (olanzapine was added to psychotherapy, n = 24); Schulz et al 33 (n = 314); Soler et al 34 (all patients were in DBT, n = 60); Zanarini and Frankenberg 35 (n = 28); and Eli Lilly 36 (n = 301). Of the remaining three studies, one compared olanzapine to haloperidol (Shafti and Shahveisi, 37 n = 28); one compared olanzapine to sertraline (Jariani et al, 10 n = 120 [all patients were on methadone maintenance therapy]); and one with three different arms of treatment 38 compared olanzapine to fluoxetine (n = 30), then olanzapine to olanzapine plus fluoxetine (n = 31), and finally fluoxetine to fluoxetine and olanzapine (n = 29).…”
Section: Olanzapinementioning
confidence: 99%
“…Soler et al [48] reported a 12week trial of olanzapine (mean dose 8.83 mg/day) versus pla cebo in 60 BPD outpatients, who received a con comitant psychotherapy with DBT. Olanzapine was superior to placebo in reducing anxiety, depressive symptoms and impulsiveaggressive behaviors.…”
Section: Olanzapinementioning
confidence: 99%
“…Among novel antipsychotics olanzapine is the most extensively studied across case-reports [10], open-label studies [11,12] and double-blind controlled trials (RCT) of patients with a diagnosis of BPD [13][14][15][16][17][18][19][20][21]. Antipsychotic drugs may owe their therapeutic efficacy to actions at D2-D4 and 5HT-2A receptors, while adverse effects are believed to be induced by antagonist activity at H1, M1-M5, and α1 receptors [22].…”
Section: Introductionmentioning
confidence: 99%
“…To date, ten RCTs have been conducted in samples with BPD to assess the efficacy of olanzapine versus placebo [13,16,23,19,21], versus active drugs [14,17,20], or versus placebo in a combined treatment with psychotherapy (dialectical behavioral therapy) [15,18]. The majority of accumulated evidence suggests that olanzapine is efficacious in treating cognitive-perceptual symptoms (psychotic-like symptoms), and in producing significant reduction in mood instability and impulsive behavioral dyscontrol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation